Revising blood pressure classification guidelines: A call for normal lower limits in the "American college of cardiology/American heart association task force on clinical practice guidelines for hypertension" - Ersin Akpinar (Archives of Clinical Hypertension - Peertechz Publications, 2023)
The existing blood pressure classification guidelines established by the American College of Cardiology/American Heart Association (ACC/AHA) and European Society of Cardiology/European Society of Hypertension (ESC/ESH) lack specified lower limits for the "Normal" category. This paper underscores the imperative need for revisiting these guidelines to incorporate defined lower limits for the "Normal" classification. The absence of such lower limits hinders the precision of clinical practice and undermines the comprehensive assessment of blood pressure in individuals. By advocating for the inclusion of lower limits, this paper aims to enhance the accuracy of blood pressure categorization, thereby providing clinicians with more nuanced guidance and fostering improved cardiovascular health outcomes.